2016
DOI: 10.1016/j.jqsrt.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Filter-based measurements of UV–vis mass absorption cross sections of organic carbon aerosol from residential biomass combustion: Preliminary findings and sources of uncertainty

Abstract: a b s t r a c tCombustion of solid biomass fuels is a major source of household energy in developing nations. Black (BC) and organic carbon (OC) aerosols are the major PM 2.5 (particulate matter with aerodynamic diameter smaller than 2.5 μm) pollutants co-emitted during burning of these fuels. While the optical nature of BC is well characterized, very little is known about the properties of light absorbing OC (LAOC). Here, we report the mass-based optical properties of LAOC emitted from the combustion of four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 58 publications
2
27
1
Order By: Relevance
“…Carbonaceous aerosol source profiles are useful for source apportionment, and they may also have implications for climate and health impact assessments. In a previous study (Pandey et al, 2016), we reported that light-absorbing OC may play a larger role in light absorption by cookstove emissions than that from earlier work on biomass burning in the USA. The difference in constituents of OC emissions from the two sources might contribute to the observed difference in their optical characteristics since thermal stability is known to be inversely related to the light absorption efficiency of organic compounds (Andreae and Gelencsér, 2006;Saleh et al, 2013).…”
Section: Resultsmentioning
confidence: 56%
“…Carbonaceous aerosol source profiles are useful for source apportionment, and they may also have implications for climate and health impact assessments. In a previous study (Pandey et al, 2016), we reported that light-absorbing OC may play a larger role in light absorption by cookstove emissions than that from earlier work on biomass burning in the USA. The difference in constituents of OC emissions from the two sources might contribute to the observed difference in their optical characteristics since thermal stability is known to be inversely related to the light absorption efficiency of organic compounds (Andreae and Gelencsér, 2006;Saleh et al, 2013).…”
Section: Resultsmentioning
confidence: 56%
“…For bituminous coal, AAEs were similar for hv‐coal (1.19 ± 0.04) and lv‐coal (1.26 ± 0.04) emissions. These AAEs, all >1.0, suggest that particulate matter emitted from both crop residues and coal burning might contain BrC (X. Li et al, ; Pandey et al, ; Shen et al, ; J. Sun et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…These AAEs, all >1.0, suggest that particulate matter emitted from both crop residues and coal burning might contain BrC (X. Pandey et al, 2016;Shen et al, 2016;J. Sun et al, 2017).…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 91%
“…MAE p of biomass burning (BB) samples is highly varied due to a wide range of fuel types and combustion conditions (Reid et al, 2005;Roden et al, 2006). A range from 6.1 to 80.8 m 2 g −1 was reported for BB MAE p at 550 nm (Pandey et al, 2016). Without the knowledge of source contributions, it is not feasible to derive a representative MAE p for E abs estimation.…”
Section: Introductionmentioning
confidence: 99%